UNRAVELING THE DEMOGRAPHIC PATTERNS OF ADOLESCENTS’ MENTAL HEALTH - Zahyreen Kousar & Zainab Hussain Bhutto (Pakistan Journal of Psychology, 2023)
The current research aimed to examine the demographic patterns of adolescents’ mental health focusing on emotional, psychological and social well-being. Using purposive sampling strategy, a sample of 609 participants (344 males & 265 females) with an age range of 15 to18 years (M=15.78, SD, .994) using the Mental Health Continuum Short Form (MHC-SF; Keyes, 2009) was collected from different private schools and colleges in Karachi, Pakistan. Descriptive and inferential statistics were used. Results reveal that 48.3% adolescents have a flourishing mental health, 46.8% haves languishing mental health and 4.9% have moderate mental health. Further, significant gender differences are evident on mental health continuum and social wellbeing. No significant association of family structure with mental health and well-being dimensions is found. Moreover, significant agewise differences are found on the mental health continuum as well as emotional and social well-being. The 15-years old adolescents were found to have better mental health than 16, 17 and 18 years age group. The findings have important implications and suggest avenues for future research.